Digital Transformation of the Construction Industry: A Review - Musarat, M.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
The construction industry is hailed as the driver for the economic development of every country to a great extent due to its dynamic nature, yet it needs digital transformation to align with the fast-paced digital world economy. Hence, to evaluate the potential for the digital transformation of various segments of the construction industry, a systematic review was conducted in this study. English research articles were extracted from the Scopus database by using keywords of 'Digital Transformation' AND 'Construction Industry' correlated to the engineering field. After a detailed screening process as per the PRISMA statement, only 26 articles were selected for further assessment from a total of 67 extracted articles. The extracted articles were focusing on digital technologies e.g., Building Information Modeling (BIM), Smart Devices, Internet of things (IoT), Drones, Project studio (PS), and digital twins and their implication in the digital transformation of the construction industry. It was evident that digital transformation enhanced the productivity and efficiency of construction projects with better control over cost, time, and risk throughout the project life cycle. Therefore, it is recommended to establish top management interest for digital partnering with trusted organizations enabling the realization of digital technologies in the construction industry. Â© 2021 IEEE.